Intranational Home Bias: Some Explanations - Hillberry, Russell; Hummels, David (The Review of Economics and Statistics, 2003)
Wolf demonstrates that trade within the United States appears substantially impeded by state borders. We revisit this finding with improved data. We show that much intranational home bias can be explained by wholesaling activity. Shipments by wholesalers are much more localized within states than shipments from manufacturing establishments. Controlling for relative prices and the use of actual, rather than imputed, shipment distances also reduces home bias estimates.